Problem-Based E-Module for Enhancing Fifth-Grade Critical Thinking in Integrated Science and Social Studies - Muhammad Ilham Setiadi; Dwi Yulianti; Fatkhur Rohman; Rangga Firdaus (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: This research project originated from an examination of the requirements of both teachers and students in their learning experiences. Its primary goal was to develop a sound, usable, and impactful problem-based e-module to improve critical thinking abilities in fifth-grade Integrated Science and Social Studies (IPAS). The study followed a Research and Development (R&D) framework, specifically the ADDIE model's five stages: Analysis, Design, Development, Implementation, and Evaluation. Participants were carefully chosen using purposive sampling to align with the research aims. Data was gathered through validated and reliable assessments and subsequently analyzed with an independent t-test, which showed a significant result (p < 0.001). The findings clearly demonstrate that the developed problem-based e-module is an effective tool for cultivating critical thinking skills in fifth-grade integrated science and social studies education. Abstrak: Proyek penelitian ini berasal dari pemeriksaan terhadap kebutuhan guru dan siswa dalam pengalaman belajar mereka. Tujuan utamanya adalah untuk mengembangkan e-modul berbasis masalah yang solid, dapat digunakan, dan berdampak untuk meningkatkan kemampuan berpikir kritis pada pembelajaran IPAS Terpadu kelas lima. Penelitian ini mengikuti kerangka Research and Development (R&D), khususnya lima tahap model ADDIE: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Partisipan dipilih secara cermat menggunakan teknik purposive sampling agar sesuai dengan tujuan penelitian. Data dikumpulkan melalui asesmen yang telah divalidasi dan reliabel, kemudian dianalisis menggunakan uji t independen yang menunjukkan hasil signifikan (p < 0.001). Temuan menunjukkan secara jelas bahwa e-modul berbasis masalah yang dikembangkan merupakan alat yang efektif untuk menumbuhkan keterampilan berpikir kritis dalam pendidikan IPAS terpadu kelas lima.